Lightweight Logging for Lazy Release Consistent Distributed Shared Memory - Costa, Manuel; Guedes, Paulo; Sequeira, Manuel; Neves, Nuno; Castro, Miguel (Proceedings of the 2nd USENIX Symposium on Operating Systems Design and Implementation (OSDI'96), 1996)
This paper presents a new logging and recovery algorithm for lazy release consistent distributed shared memory (DSM). The new algorithm tolerates single node failures by maintaining a distributed log of data dependencies in the volatile memory of processes. The algorithm adds very little overhead to the memory consistency protocol: it sends no additional messages during failure-free periods; it adds only a minimal amount of data to one of the DSM protocol messages; it introduces no forced rollbacks of non-faulty processes; and it performs no communication-induced accesses to stable storage. Furthermore, the algorithm logs only a very small amount of data, because it uses the log of memory accesses already maintained by the memory consistency protocol. The algorithm was implemented in TreadMarks, a state-of-the-art DSM system. Experimental results show that the algorithm has near zero time overhead and very low space overhead during failure-free execution, thus refuting the common belief that logging overhead is necessarily high in recoverable DSM systems.